ESTUDIO DEL PERFIL DE FORMACIÓN DE LOS PRODUCTORES Y DIRECTORES PARA LA EJECUCIÓN DE PROYECTOS AUDIOVISUALES. - LOPEZ ALAVA, RAISSA ELOISA (2024)
ABSTRACT The present research work was carried out with the objective of analyzing the training profile of producers and directors of Audiovisual Projects in order to understand the needs present in the training of professionals in the production and direction of Audiovisual Projects. The presentation of this project provides a deep understanding of the demands of the labor market and the current expectations in the audiovisual industry with direct relation to the academic training of audiovisual producers and directors in order to create more effective educational programs that allow the development of new skills and abilities in future professionals. It also emphasizes the similarity of certain subjects in the careers of Multimedia, Performing Arts and Film in comparison with the career of Social Communication, which shows that by sharing training characteristics they can also share work space in areas of development of innovative audiovisual projects, making use of new technologies and current trends to entertain, inform and educate people through Audiovisual Projects and their implementation in various areas of education and entertainment.